Groundwater surface water interactions and the role of phreatophytes in identifying recharge zones - Ahring, Trevor S.; Steward, David R. (My University, 2012)
Groundwater and surface water interactions within riparian corridors impact the distribution of phreatophytes that tap into groundwater stores. The changes in canopy area of phreatophytes over time is related to changes in depth to groundwater, distance from a stream or river, and hydrologic soil group. Remote sensing was used to determine the location of trees with pre-development and post-development aerial photography over the Ogallala Aquifer in the central plains of the United States. It was found that once the depth to groundwater becomes greater than about 3 m, tree populations decrease as depth to water increases. This subsequently limited the extent of phreatophytes to within 700 m of the river. It was also found that phreatophytes have a higher likelihood of growing on hydrologic soil groups with higher saturated hydraulic conductivity. Phreatophytes exist along portions of the Arkansas River corridor where significant decreases in groundwater occurred as long as alluvium exists to create perched conditions where trees survive dry periods. Significant decreases (more that 50%) in canopy cover exists along river segments where groundwater declined by more than 10 m, indicating areas with good hydraulic connectivity between surface water and groundwater. Thus, interpretation of changes in phreatophyte distribution using historical and recent aerial photography is important in delineating zones of enhanced recharge where aquifers might be effectively recharged through diversion of surface water runoff.
Keywords: Groundwater; Phreatophytes; Riparian corridors